Analytical and numerical investigation on increasing shooting range with muzzle brake optimization of MPT-76 lLight machine gun - Dilbaz, Hakan (My University, 2023)
Günümüzde savunma sanayi hızla gelişim göstermektedir. Araştırma geliştirme süreçlerinden, üretim süreçlerine kadar yüksek teknolojilerin kullanıldığı savunma sanayi alanında, Türkiye’ye özgün ve yerli ürünler üretebiliyor olmak, diğer ülkelere bağımlılığı engellemek amacıyla önem arz etmektedir. Bu amaçla tasarlanan ve 2014 yılında Türk Silahlı Kuvvetleri envanterine katılan MPT-76 hafif makineli tüfeği, Makine ve Kimya Endüstrisi tarafından üretilen yerli ve milli ilk hafif makineli piyade tüfeğidir. Sahip olduğu düşük ve yüksek sıcaklıklarda, çamurlu, tozlu arazide çalışma gibi kabiliyetlerle 42 ayrı teste tabii tutularak kalifiye edilmiştir. Bu yetenekleri ile Dünya’da hafif makineli tüfekler arasında kendine üst sıralarda yer bulan milli piyade tüfeği, MPT-76 iyileştirme faaliyetlerine TSK’nın geri bildirimleri doğrultusunda halen devam edilmektedir. Farklı kalibreye yani mermi çapına sahip bütün silahların geliştirilmesi aşamasında, atılan merminin ulaşabileceği maksimum mesafeye gitmesi hedeflenmektedir. Merminin menziline etki eden faktörler silahın iç ve dış balistik parametrelerine göre değişkenlik göstermektedir. Bu parametrelerden bazıları; mühimmat tipi, namlu tipi, namlu malzemesi, namlu iç, dış basınç ve sıcaklık değerleri, namlu cidar kalınlığı ve namlu freni gibi silah tasarımına bağlı parametrelerdir. Bu kapsamında, MPT-76 tüfeğinin namlu freni sayısının optimize edilmesiyle silahtan çıkan mühimmatın menzilinin maksimum mesafeye ulaşması analitik ve nümerik olarak incelenecektir. Silah tetiğine basılmasıyla barut ateşlendikten sonra, mühimmatın namludan çıkış hareketi, zamana bağlı olarak Ansys Fluent kullanılarak 6 farklı namlu freni adımına sahip tasarım, sonlu hacimler nümerik yöntemiyle analiz edilerek, sonuçları karşılaştırılacaktır. Çalışmanın daha iyi anlaşılması ve yapılacak olan hesaplama ile analizlerin dayanağı olarak, silah iç balistiği etkileyen ana denklemler irdelenecektir. Hafif silahlar için mühimmat bilgilerine ait veriler ve atış menzili hesaplama yöntemleri de ayrıca incelenecektir. Çalışma sonunda, namlu freni sayısı optimize edilerek MPT-76 hafif makineli tüfeğinin daha uzun menzilli atışlar yapması amaçlanmaktadır.

Today, the defence industry is developing rapidly. In the defence industry, where high technologies are used from research and development processes to production processes, being able to produce original and domestic products in Turkey is critically important in order to prevent foreign dependency. The MPT-76 light machine gun, designed for this purpose and provided to the inventory of the Turkish Armed Forces in 2014, by Mechanical and Chemical Industry. It is the first local and national submachine gun produced by the company. It has been qualified by being subjected to 42 separate tests with its abilities such as working at low and high temperatures, working in muddy and dusty terrain. With these capabilities, the national infantry rifle, which ranks among the top among light machine guns in the world, is still continuing its MPT-76 improvement activities in line with the feedback of the TAF. In the development phase of all weapons with different calibres, it is aimed that the projectile will go to the maximum distance it can reach. The factors affecting the range of the bullet vary according to the internal and external ballistic parameters of the weapon. Some of these parameters are; ammunition type, barrel type, barrel material, barrel internal/ external pressure and temperature values, barrel wall thickness and muzzle brake. Within the scope of this master's thesis study, the maximum range of the ammunition coming out of the weapon by optimizing the muzzle brake fin step of the MPT-76 light machine gun will be investigated analytically and numerically. After the gunpowder is fired by pressing to trigger, the movement of the bullet from the muzzle outlet will be analysed using the Ansys Fluent depending on time. Meanwhile, muzzle brake designs that has 6 different fin steps will be analysed using the finite volume method and the results will be compared. As the basis of better understanding of the study, the basic equations affecting the internal ballistics of the weapon will be examined that have used through calculations and analysis. Ammunition information and range calculation methods will also be conveyed for light machine gun too. It is aimed that the shooting range of the MPT-76 light machine gun will be longer by optimizing the number of muzzle brakes.
Keywords: Atış Menzili; Defense industries; Hafif makine tüfek; Interrior Ballistics; İç Balistik Light machine gun; MPT-76; Muzzle Brake; Namlu Freni; Savunma endüstrileri; Shooting Range; Turkey; Türkiye